Cathodic Synthesis of Cinnamic Aldehyde - Madhu, Ms. (Asian Journal of Chemistry, 2010)
Cinnamic aldehyde has been synthesized by cathodic reduction of cinnamic acid at zinc and amalgamated copper electrodes using galvanostatic method. Polarization curves obtained in the presence and absence of depolarizer indicated the proper range of current densities to be investigated. Isolated product was characterized by TLC and NMR spectral analysis. Effect of various parameters like current density, temperature and nature of cathode material on yield percentage have been investigated.